CCL20 is a potential therapeutic target associated with immune infiltration in breast cancer - Zhai, Hongyan; Zhang, Na; Mo, Dan; Qin, Tingting (Journal of international medical research, 2023)
Objectives CCL20 is a chemotactic factor that is involved in immune cell recruitment and cancer progression. However, the role of CCL20 in the prognosis of breast cancer remains unclear. This study analyzed correlations between CCL20 expression and immune infiltration, clinicopathological parameters, and prognosis in breast cancer patients. Methods Correlations between CCL20 expression and clinicopathological parameters, prognosis, and immune infiltration in breast cancer were determined using the TIMER, UALCAN, and PrognoScan databases. Furthermore, gene–gene and protein–protein interactions were determined using GeneMANIA and STING network construction, respectively. Results CCL20 expression was significantly upregulated in breast cancer and had significant associations with clinicopathological features, including race, sex, age, menopause status, cancer stage, cancer subclass, and nodal metastasis; moreover, patients with higher CCL20 expression exhibited poor prognosis. Meanwhile, CCL20 expression was significantly correlated with the infiltration of immune cells in breast cancer, including monocytes, neutrophils, tumor-associated macrophages, Th1 cells, regulatory T cells, and exhausted T cells. Moreover, the network of CCL20 expression showed the majority genes and proteins were associated with immune reactions. Conclusions CCL20 is a prognosis-related biomarker in breast cancer on the basis of its correlation with immune infiltration levels and has potential to also be a therapeutic target.